2018
DOI: 10.18311/mvpjms/2018/v5/i1/10320
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study on Etiology, Onset and Clinical Manifestations of Neonatal Seizures

Abstract: Background: Neonatal seizures are clinically significant because very few are idiopathic. Further investigation leading to prompt diagnosis of the underlying condition is important because many of the etiologies have specific treatment. Time of onset of seizures has correlation with etiology. Objectives: The objective of the present study is to know the etiology of neonatal seizures, to know the time of onset of neonatal seizures and its relation to etiology and to know the various types of seizures in neonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In another study conducted by Patil et al (2018), onset of seizures was found to be within irst 3 days of life in 101(79.5%) neonates while after 3 days of life, only 26 (20.5%) neonates developed seizures. It was also concluded that, onset of seizures within irst 3 days of life of had statistically signi icant correlation with birth asphyxia being the causative factor with p<0.001…”
Section: Discussionmentioning
confidence: 92%
“…In another study conducted by Patil et al (2018), onset of seizures was found to be within irst 3 days of life in 101(79.5%) neonates while after 3 days of life, only 26 (20.5%) neonates developed seizures. It was also concluded that, onset of seizures within irst 3 days of life of had statistically signi icant correlation with birth asphyxia being the causative factor with p<0.001…”
Section: Discussionmentioning
confidence: 92%